Health-promoting activities among Saudi Arabian parents of children with disabilities: A cross-sectional study - Alghamdi, Salmah A.; Assiri, Muna I.; Fallatah, Reem A.; Albeladi, Farah M.; Alabdulaziz, Hawa; Alsaggaf, Fatimah (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Engaging in health-promoting activities is crucial for maintaining overall well-being. However, parents of children with disabilities often face unique challenges that can impact their ability to engage in such activities. These challenges may include increased caregiving responsibilities, limited access to resources, and emotional and physical burdens, which may hinder their involvement in health-promoting behaviors. Objective: This study aimed to assess and compare health-promoting activities among parents of children with and without disabilities, with a focus on identifying key differences and associated factors that influence their health and well-being. Methods: A quantitative cross-sectional study was conducted with 118 parents of children aged 3 to 18 years recruited via social media and centers for children with disabilities in the Kingdom of Saudi Arabia. Data were collected using the eight-item Health-Promoting Activities Scale (HPAS) and demographic variables. The study utilized descriptive statistics, chi-square test, t-test, and ANOVA for data analysis, conducted using SPSS version 25. Results: The results showed that parents of children with disabilities had significantly lower HPAS scores (31.73 ± 10.21) compared to parents of children without disabilities (34.83 ± 8.05), although this difference was not statistically significant (p = 0.082). Parents of children with disabilities reported significantly lower frequencies of spiritual or rejuvenating personal time (p = 0.032) and social activities (p = 0.011). Additionally, higher education (p = 0.023) and better health status (p = 0.005) were positively associated with higher HPAS scores among parents. Conclusion: This study’s findings highlight the significant impact that caring for a child with a disability can have on parents’ health-promoting behaviors. Factors such as education and health status were found to play a crucial role in shaping these behaviors. The results suggest the need for tailored interventions and support programs by nurses and healthcare providers to enhance the well-being of parents of children with disabilities.